Exploration of Jepara Carving Ethnomatics and Its Implementation in Geometry Learning Junior High School - Siti Aminah; Syamsuri Syamsuri (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
This study aims to explore the ethnomathematics of Jepara carving and its implementation in learning geometry, especially at the junior high school level. This type of research is qualitative research with an ethnographic approach. Subjects/resource persons in this study were Jepara carving craftsmen in the city of Rau Jepara. The research instrument is the researcher as the main instrument, observation, interviews, and documentation. Based on the results of research on the ethnomathematics of Jepara carving shows that there are basic mathematical activities in the mindset that is applied to the process of making Jepara bones related to measurement, calculation, and design, as well as geometric concepts such as angles, squares, rectangles, rhombuses, triangles, and circles. The implementation of ethnomathematical learning based on Jepara carving, especially geometry learning that can be applied in schools is learning material in the form of a collection of contextual questions related to the local culture of Jepara carving on angles and flat shapes studied in Junior High School Education.